Jack's life : a Taylorean auto/biographical study of the masculine identity of a young Irish male undergraduate - O'Donoghue, Connor Tiarnach (Trinity College (Dublin, Ireland). School of Education, 2015)
Masculinities is a relatively new field of study, grounded in anthropology, sociology and psychoanalysis. The most cited author in the field, Raewyn Connell, has developed a widely-used sociological theory of masculinities, based around the concepts of hegemony, complicity, subordination, authorisation and marginalisation structured in socially and culturally-specific gender regimes.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin